The manual pressures of stone tool behaviors and their implications for the evolution of the human hand. Issue 119 (June 2018) - Williams-Hatala, Erin Marie; Hatala, Kevin G.; Gordon, McKenzie; Key, Alastair; Kasper, Margaret; Kivell, Tracy L.
Abstract: It is widely agreed that biomechanical stresses imposed by stone tool behaviors influenced the evolution of the human hand. Though archaeological evidence suggests that early hominins participated in a variety of tool behaviors, it is unlikely that all behaviors equally influenced modern human hand anatomy. It is more probable that a behavior's likelihood of exerting a selective pressure was a weighted function of the magnitude of stresses associated with that behavior, the benefits received from it, and the amount of time spent performing it. Based on this premise, we focused on the first part of that equation and evaluated magnitudes of stresses associated with stone tool behaviors thought to have been commonly practiced by early hominins, to determine which placed the greatest loads on the digits. Manual pressure data were gathered from 39 human subjects using a Novel Pliance ® manual pressure system while they participated in multiple Plio-Pleistocene tool behaviors: nut-cracking, marrow acquisition with a hammerstone, flake production with a hammerstone, and handaxe and flake use. Manual pressure distributions varied significantly according to behavior, though there was a tendency for regions of the hand subject to the lowest pressures (e.g., proximal phalanges) to be affected less by behavior type. Hammerstone use during marrow acquisition and flake production consistently placed the greatest loads on the digits collectively, on each digit and on each phalanx. Our results suggest that, based solely on the magnitudes of stresses, hammerstone use during marrow acquisition and flake production are the most likely of the assessed behaviors to have influenced the anatomical and functional evolution of the human hand.